Report of the Technical Committee for the Optimum Utilisation of the Krishna and the Godavari Waters and Connected Papers 1953 - Planning Commission (Planning Commission Government of India, 1953)
This summary synthesizes the findings of the Technical Committee appointed by the Planning Commission to examine the optimum utilization of the Krishna and Godavari river waters, with particular emphasis on irrigation development in the Madras and Hyderabad regions. The report evaluates hydrological characteristics, proposed dam and canal systems, and phased project alternatives, including the Krishna-Pennar, Nandikonda, Siddeswaram, and Pulichintala schemes. It highlights the potential for expanding irrigation in drought-prone areas while addressing financial viability, inter-basin water transfers, and environmental and social impacts such as displacement. The committee advocates a staged and integrated approach to water resource management, balancing food security, regional equity, and economic feasibility. Overall, the report provides a foundational framework for sustainable irrigation planning and coordinated development in the Krishna–Godavari river basins.
India Planning Commission
Keywords: Krishna River Basin; Godavari River Basin; Irrigation Projects; Water Resource Management; Krishna-Pennar Project; Dam Construction; Agricultural Productivity; Regional Development; Hydrological Assessment; Cost–Benefit Analysis; Displacement and Rehabilitation; Integrated Planning